Investigation of biodegradable metal for Urological Applications - Rodriguez Martinez, Allison Yineth (Escuela Colombiana de Ingeniería Julio Garavito, 2020)
Temporary medical implants made of degradable metals have been studied due to their safely dissolving in the human body. Zinc based alloys are the alternative to overcome the limitations of magnesium and iron samples in physiological environment. In this study, the characterisation of mechanical properties, determination of the degradation resistance in artificial urine (AU) for electrochemical and immersion tests, and analysis of the elemental composition of the corrosion layer were carried out in pure Zn samples (wire and sheet). The corrosion rates obtained were affected by the presence of the ZnO. Non-uniform corrosion of Zn was observed and Ca in the corrosion layer is an undesirable result. Moreover, the diameter reduction for Zn wire samples displayed a relationship between mass loss and immersion time. This work shows significant results to take account in further studies in the urological field; however, mechanical properties and corrosion behaviour of pure Zn samples need to be improved.

Los implantes médicos temporales hechos de metales degradables se han estudiado debido a su disolución segura en el cuerpo humano. Las aleaciones a base de zinc son la alternativa para superar las limitaciones del magnesio y el hierro en el entorno fisiológico. En este estudio, la caracterización de las propiedades mecánicas, la determinación de la resistencia a la degradación en orina artificial en pruebas electroquímicas y de inmersión, y el análisis de la composición elemental de la capa de corrosión se llevaron a cabo en muestras de Zn puro, en alambre y en lámina. Las tasas de corrosión obtenidas se vieron afectadas por la presencia de ZnO. En las muestras se observó corrosión no uniforme y la presencia de Ca en la capa de corrosión es un resultado indeseable. Además, la reducción del diámetro de las muestras de alambre de Zn mostró una relación entre la pérdida de masa y el tiempo de inmersión. Este trabajo muestra resultados significativos a tener en cuenta en futuros estudios en el campo urológico; sin embargo, las propiedades mecánicas y el comportamiento a la corrosión de las muestras de Zn puro deben mejorarse.
Keywords: Biodegradables-metales; Orina artificial; Aplicaciones Urológicas; Biodegradable-metals; Artificial urine; Urological Applications